Enhancing Learners' Motivation and Concern for Improving their Pronunciation at a Translator Program in Argentina - Pedro Luchini (Asociación Colombiana de Profesores de Ingles, 2006)
This paper aims to evaluate the implications of using collaborative assessment in an English language course (LII) with a pronunciation component at an English/Spanish Translator Program, Universidad CAECE (the University), Argentina. The participants of this study were 17 students whose L1 was Spanish. In this research, the students recorded their speech, listened to it and then transcribed it. Later, they graded their own performance and compared their outcomes with those coming from their teacher's assessment results. Data were gathered from the learners' achievements and their self-assessment reports. The findings revealed that after completing this activity, the learners developed a major concern and motivation to improve their L2 oral communicative skills. Based on these findings, some recommendations for further research were given.